Decision aiding for lower soil risk in urban planning operation. Issue 4 (1st October 2016) - Taillandier, Franck; Breysse, Denys
ABSTRACT: Urban development projects carry major issues and are also subject to significant risks. Soil (surface and underground) can be the source of uncertainties that may induce risks. Soil risks are often reduced by experts to geotechnical issues. The SORIA method (SOil RIsk Analysis for urban planning project) was developed into the ANR-D2SOU project to integrate a more comprehensive analysis related to soil/subsoil since the early stages of the project. More specifically, SORIA is a risk analysis method, considering soil/subsoil evaluation methods to optimise the project from this perspective. For this purpose, SORIA uses a utility-based approach coupled with a risk knowledge base. This method has been experimented on a real case, which is presented in this paper.